Strategies of survival, livelihood, and resistance in transit: a narrative analysis of the migration trajectory of a Guinean asylum seeker in France - De Jesus, Maria; Warnock, Bronwyn; Moumni, Zoubida; Hassan Sougui, Zara; Pourtau, Lionel (Frontiers in Human Dynamics, 2024)
The concept of 'transit' is an understudied phenomenon in migration studies. Transit is not necessarily a linear and unidirectional temporal movement from origin to destination countries, nor is it a clearly demarcated event in time and space. This article examines the complex dimensions of transit, that is, the geospatial, social, economic, psychological, and relational aspects that both shape and are being shaped by asylum seekers. Drawing on a unique qualitative phenomenological approach, the study utilizes an in-depth case narrative to trace and analyze the transit of Mamadou, a Guinean 26-year-old male asylum seeker in France. The salient themes of the narrative fall into five parts: (1) Triggers of transit; (2) Transit as a survival strategy; (3) The complex legal hurdles of asylum; (4) The politics of discomfort and dispersal; and 5) Acts of resistance. Throughout the narrative, an analytic lens is interwoven as informed by relevant literature. The results highlight how Mamadou's migration trajectory is characterized by various cycles of trauma, while he simultaneously employs survival, livelihood, and resistance strategies to confront and overcome these different forms of trauma. This paper highlights the muchneeded call to depoliticize transit through adopting a pragmatic approach to asylum that promotes a virtuous cycle of policies, which contribute to the well-being and integration of asylum seekers.